(untitled) (Baghdad Science Journal, 2014)
The antioxidant and antibacterial activities of ethanolic extract and phenolic compounds extract of Lemon balm (Melissa officinalis) and Oregano (Oreganum vulgare) plants were studied; the phenolic content and the relationship between these compounds and the above activities were also investigated. The results showed that the Lemon balm had the highest phenolic content (56.5% mg g) and the phenolic content of Oregano was twice lower than Lemon balm. Lemon balm has the highest antioxidant activity which causes lipid peroxidation inhibition activity of linoleic acid (90.5%), this activity was more than ?-tocopherole antioxidant activity (79.3 %). It was found that the main source of antioxidant activity of these plants was belonging to phenolic compounds and the results proved the strong relationship between antioxidant activity and phenolic content. The ethanolic extract of Lemon balm was exhibited strong antibacterial activity ,the inhibition included all bacterial isolates , with highest inhibition zone against Bacillus cereus ( 26 mm), while Oregano did not exhibit clear antibacterial activity, Aeromonas hydrophila was the most resistant isolate . It was obvious from the results of effect of phenolic compounds on bacteria that no relationship between antibacterial activity and phenolic content and the inhibition may be due to other compounds.